Theoretical Investigation of the Passive Transmitter Based on Reconfigurable Metasurface - Yang, Shuai; Zhang, Kuang; Ding, Xumin; Yang, Guohui; Wu, Qun (Frontiers in Physics, 2021)
Wireless communication has become a standard solution to satisfy ever-increasing demands for information transfer in our daliy life. Further more, reconfigurable metasurfaces comprised of multiple tunable unit cells have drawn significant attentions due to their superior electromagnetic performance, with the desired electromagnetic response can be controlled by computer.So we present a prototype of wireless communication system based reconfigurable metasurface that works in the microwave frequency range. A 2-D periodical array of reconfigurable metasurface is loaded with varactor diode to effectively adjust the in-band transmission and reflection coefficients the maintain different far-field electromagnetic characteristics. Since the reconfigurable metasurface does not radiate electromagnetic waves and it only carries information by adjusts its reflection and transmission coefficients. With this reconfigurable metasurface, a passive communication method can be realized.